2016
DOI: 10.1007/s11626-016-0009-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vitrified outcomes between human early blastocysts and expanded blastocysts

Abstract: We compared the vitrified outcomes between early and expanded blastocysts with or without laser drilling. The grade III embryos from the patients undergoing in vitro fertilization-embryo transfer (IVF-ET) in our reproductive center from September 2009 to February 2015 were incubated into early blastocysts and expanded blastocysts. The early blastocysts and expanded blastocysts were, respectively, divided into laser group (vitrification after laser drilling), non-laser group (direct vitrification), and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Blastocoele collapse can be achieved mechanically by aspiring the blastocoele liquid with a micropipette or by inducing a releasing of this liquid using a laser shot 22,34 . Several studies have shown that high-quality early blastocyst embryos (G1 and G2) do not systematically develop to viable fully expanded blastocyst able to hatch and implant 29,32,35 . The advantage of using fully expanded blastocyst is associated with the fact that these embryos may have been selected further through culture and thus have a higher implantation and live birth rates than less expanded ones (G1, G2).…”
Section: Discussionmentioning
confidence: 99%
“…Blastocoele collapse can be achieved mechanically by aspiring the blastocoele liquid with a micropipette or by inducing a releasing of this liquid using a laser shot 22,34 . Several studies have shown that high-quality early blastocyst embryos (G1 and G2) do not systematically develop to viable fully expanded blastocyst able to hatch and implant 29,32,35 . The advantage of using fully expanded blastocyst is associated with the fact that these embryos may have been selected further through culture and thus have a higher implantation and live birth rates than less expanded ones (G1, G2).…”
Section: Discussionmentioning
confidence: 99%
“…All these AS methods have been shown to improve blastocyst survival rate, implantation rate and pregnancy rate [7, 9, 11, 12, 17, 18]. However, only a few studies focused on the comparison of these AS methods when applied prior to vitrification.…”
Section: Discussionmentioning
confidence: 99%